Financial Flexibility, Bank Capital Flows, and Asset Prices - PARLOUR, CHRISTINE A.; STANTON, RICHARD; WALDEN, JOHAN (Journal of Finance, 2012)
ABSTRACT In our parsimonious general‐equilibrium model of banking and asset pricing, intermediaries have the expertise to monitor and reallocate capital. We study financial development, intraeconomy capital flows, the size of the banking sector, the value of intermediation, expected market returns, and the risk of bank crashes. Asset pricing implications include: a market's dividend yield is related to its financial flexibility, and capital flows should be important in explaining expected returns and the risk of bank crashes. Our predictions are broadly consistent with the aggregate behavior of U.S. capital markets since 1950.